Companies Law No. 159/1981 As amended up to January 2004 / Translated by The middle east library for economic services. - The middle east library for economic services, translator. (2025)
Part - I : General Provisions. - Chapter: 1 Companies ruled by the provisions of the present law. - Chapter: 2 The foundation. -- Part - II : Provisions Relating To The Kinds Of Companies. - Chapter : 1 Shareholder Companies. - Chapter : 2 Commandite Companies with shares. - Chapter : 3 Limited Liability Companies. -- Part - III: Incorporation and Change of The Form Of The Company 1. Incorporation. 2. Change of the form of the Company -- Part - IV: Liquidation of The Company. -- Part - V: 1. Control. 2. Inspection. 3. Penalties. -- Part - VI: Branches and Offices of Foreign Companies in Egypt. 1. Branches of foreign companies and analogous establishments. 2. Representative offices and their analogies. -- Part - VII: Conclusive Provisions. 1. Provisions concerning the workers in the company. 2. Restrictions relating to workers in the State and members of the representative organization. 3. Diverse provisions and transitory articles. 4. Ministerial Decree No. 850/2001 implementing certain provisions of law No. 3/1998.